Effect of DIC Technology on Phenolic Content and Antioxidant Activity of Rheum ribes L. rhizome Extracts. Issue 2 (September 2022) - Aad, Elizabeth Abi; Karaky, Racha; Besombes, Colette; Haddad, Joseph; Allaf, Karim
No abstract available